Pelatihan Pemanfaatan Artificial Intelligence dalam Pembelajaran Siswa di SMAN 12 Denpasar - Ida Bagus Ardhi Putra; I Made Dwi Hita Darmawan; Kurniawan Joko Purnomo (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The advancement of artificial intelligence (AI) requires the younger generation to possess adequate digital literacy, including the ability to utilize AI in learning contexts. Although Indonesian society has a relatively high awareness of AI, knowledge and productive usage remain limited. This community service activity aims to enhance the competencies of students at SMAN 12 Denpasar in utilizing generative AI, such as ChatGPT and Google Gemini, to support their learning processes. The activity was conducted on December 12, 2025, involving 30 twelfth-grade students through three stages: preparation (needs survey and module development), training (theoretical and practical sessions), and evaluation via online questionnaires. Results showed 92% of participants were satisfied, all reported increased understanding and skills in AI, and 100% expressed interest in continuing similar activities. The structured, practice-based approach proved effective and replicable in Indonesia's secondary education.